PROJECT-BASED LEARNING PADA MATA KULIAH KIMIA ANALITIK DASAR MENGGUNAKAN YOUTUBE UNTUK PENINGKATAN KETERAMPILAN ABAD 21 - Abraham Mora; Hokcu Suhanda; Triannisa Rahmawati (Lantanida Journal, 2022)
In recent years, the development of information and digitalization is growing very rapidly, especially in the state of distance learning due to the COVID-19 pandemic. In addition, this era leads to the need for 21st-century skills possessed by students to be survived amid several disruptions in various conventional fields. Assignments based on project-based learning have been carried out to the chemistry students at Indonesia University of Education in the Basic Analytical Chemistry course to learn the effect of project based learning using youtube as the publication media to improve various 21st-century skills. 6 videos explained the advanced methods applied in the analytical chemistry field have been resulted in. These videos were uploaded to YouTube with a total of 2662 viewers, 1577 likes, as well as 235 comments. Descriptive studies were used as a research method to get some respon from students according to the implementation of 21st-century skills. In addition, we collected qualitative respons from viewers related to the content of explanatory videos that have been made. Through a survey, around 85% of students stated agree and strongly agree that this project-based learning could improve their collaboration skill (4.34/5 scale), scientific literature literacy (4.40/5), creative thinking (4,49/5), communication (4.54/5) as well as critical thinking (4.7/5). Finally, positive and supportive respon from audiences strengthened arguments that this assignment could be exercising the teaching and communication skills of students